A real-world observational study on the effect of Qingre Lishi decoction on glycemic profile using continuous glucose monitoring in obese type 2 diabetes adults - Wei, Bingchen; Gao, Tianshu; Li, Mingzhe; Tian, Xiaojun; Wang, Jinxi (Frontiers in Endocrinology, 2024)
Objective To observe the clinical efficacy and safety of the Qingre Lishi decoction in treating of newly diagnosed overweight and obese patients with type 2 diabetes mellitus (T2DM) from an evidence-based medical perspective. Methods 70 cases of overweight and obese patients with newly diagnosed T2DM treated in the outpatient clinic of the Department of Endocrinology of the Affiliated Hospital of Liaoning University of Traditional Chinese Medicine from December 2021 to November 2022 were selected, of which 35 cases were in the observation group and 35 cases were in the control group. The observation group was treated with the Qingre Lishi decoction add lifestyle intervention, and the control group was treated with lifestyle intervention only. We compared and analyzed the fasting blood glucose (FPG), 2-hour postprandial glucose (2hPG), the occurrence of adverse reactions, and the related indexes provided by wearing the CGM device during the observation period of the patients in the two groups. Results 53 participants completed the clinical trial. In relation of glycemic control, a decreasing trend has shown in both groups, with the decreases in FPG, 2hPG, eHbA1c, and MG in the observation group being higher than those in the control group (P<0.05). In regard to blood glucose attainment, at the 28d, the attainment rate of patients in the observation group with TIR>80% was 87.10%, and the magnitude of changes in the rise of TIR and the fall of TAR was significantly better than that in the control group (P<0.01). In terms of blood glucose fluctuation, CV and SD of the patients in the observation group decreased compared with the 0d; the magnitude of daytime blood glucose fluctuation was significantly alleviated compared with that of the control group. The degree of decrease in LAGE, MAGE, and MODD was significantly lower than that of the control group (P<0.01). Conclusion The Qingre Lishi decoction can effectively improve the hyperglycemic condition of overweight and obese patients with newly diagnosed T2DM. It can reduce blood glucose, alleviate blood glucose fluctuations, reduce the incidence of hypoglycemia, and improve patients’ adherence and self-confidence in controlling blood glucose. Clinical Trial Registration https://itmctr.ccebtcm.org.cn/, identifier ITMCTR2024000006.